Suprathel-antiseptic matrix: In vitro model for local antiseptic treatment? - Ryssel, Henning; Radu, Christian Andreas; Germann, Günter; Kloeters, Oliver; Riedel, Katrin; Otte, Maximilian; Kremer, Thomas (Advances in skin & wound care, 2011)
Acetic acid is a traditional antiseptic agent that has been used for more than 6000 years. The main goal of this study was to demonstrate the suitability of Suprathel (PolyMedics Innovations GmbH, Denkendorf, Germany) in combination with various antiseptic agents to create an "antiseptic-matrix" especially designed for problematic microorganisms such as Proteus vulgaris, Acinetobacter baumannii, or Pseudomonas aeruginosa, which are frequently associated with burns. The study was designed to test the in vitro antimicrobial effect of a "Suprathel-antiseptic matrix" (Suprathel combined with acetic acid 3%, povidone-iodine 11% [Betaisodona], polyhexanide 0.04% [Lavasept], phenoxyethanol 2%/octenidine dihydrochloride 0.1% [Octenisept], mafenide acetate 5%, and chlorhexidine gluconate 1.5%/cetrimid 15% [Hibicet]). As a means to assess the typical bacterial spectrum of a burn unit, the following Gram-negative and Gram-positive bacteria strains were tested: Escherichia coli, P vulgaris, P aeruginosa, A baumannii, Enterococcus faecalis, Staphylococcus epidermidis, Staphylococcus aureus, methicillin-resistant S aureus, and β-hemolytic streptococcus groups A and B. The tests showed a positive bactericidal effect of the Suprathel-antiseptic matrix, particularly with problematic Gram-negative bacteria such as P vulgaris, P aeruginosa, and A baumannii, except for the combination of Suprathel and mafenide acetate. It can be concluded that Suprathel-antiseptic matrix appears to be suitable as a local antiseptic agent, but clinical studies need to be performed to confirm these in vitro observations. The authors' previous studies have shown that acetic acid demonstrates a wide antiseptic spectrum for microorganisms typically found in burn patients. The combination of Suprathel and acetic acid worked well in this study and appears to be promising for future clinical application.
Gesehen am 28.09.2022